Greening Corporate Reporting: An Institutional Theoretical Approach - Rowe, Anna (Asia-Pacific Conference on International Accounting Issues, 2005)
There is scarcely any conclusively ‘accepted’ theory for environmental accounting and Corporate Environmental Reporting (CER) in particular. Nevertheless, the ardent search for a new accounting vision in reporting has enriched our understanding of a wide array of views and philosophies. This paper highlights the main theories concerning CER, identifying gaps in this literature that motivate the exploring of institutional theoretical concept in understanding the motivation for CER.